Scapegoating Non-Conforming Identities: Witchcraft Hysteria in Arthur Miller’s The Crucible and Caryl Churchill’s Vinegar Tom - Yılmaz Demirkaya, Neslihan (Journal of History Culture and Art Research, 2015)
Scapegoating Non-Conforming Identities: Witchcraft Hysteria in Arthur Miller’s The Crucible and Caryl Churchill’s Vinegar Tom Abstract When people are faced with different takes on their traditions that they firmly cling to so as to remain being who they purport to be, they are generally inclined to ostracise those who are different. In this sense, ostracising people by discarding them from their community is, metaphorically speaking, the same as leaving the goat in the wilderness as the verses from Leviticus explain the history of scapegoating. Just as the goat story from Leviticus, political and patriarchal power groups blame non-conforming individuals for all the problems in society, and ostracise them as witches only to take the upper hand, and enjoy absolute power. The pattern of punishment proves to be the same, that is, to leave the victim alone in a place away from home, be it the wilderness for a goat, or the loneliness and isolation for an individual. Besides, one of the most used and most efficient ways of scapegoating people, as the evidence shows, is to rekindle the tall-tale of witchcraft. This paper explores how and why witchcraft is deployed as a scapegoating strategy to silence and stigmatise non-conforming individuals on the pretext of maintaining order in society in Arthur Miler’s The Crucible (1953) and Caryl Churchill’s Vinegar Tom (1976) respectively.